Prevalence of Bovine Immunodeficiency Virus Infection in Buffaloes in East Azerbaijan, Northwestern Iran - Kaleibar, Mohammad Tolouei-; Mozaffari, Morteza; Ashrafi, Javad; Nikbakht, Golamreza; Fathi, Ezzatollah (Journal of Buffalo Science, 2018)
Bovine immunodeficiency virus (BIV) has a worldwide distribution, but its prevalence in different regions of Iran is unknown. In this study, for the first time, the presence of BIV infections is detected by using the PCR method in Iranian water buffalo in East Azerbaijan. For this matter, blood samples were taken from 83 randomly selected buffaloes slaughtered in Tabriz industrial slaughterhouse from June to October 2012. All of the animals were clinically examined before sampling. Viral Gene-spin™ Viral DNA/RNA Extraction Kit was used to extract the DNA, and PCR was performed on the extracted DNA using oligonucleotiode primers specific for the gag gene region of the BIV virus. The prevalence of BIV in buffaloes was 2.4% (2 of 83), which is less than the prevalence of BIV in Pakistan (10.3%) and India (19%). The low prevalence observed in this study may be due to our small sample size.